Pengaruh Institutional Trust terhadap Perilaku Kooperatif dalam Konteks Penerapan Protokol Kesehatan - Ayu Krisnasari; Dewi Rosiana (Bandung Conference Series: Psychology Science, 2022)
Abstract. Covid-19 is an infectious disease caused by a coronavirus. Responding to the COVID-19 pandemic, the government is working hard to implement the 3M rules, namely wearing masks, washing hands, and maintaining distance. But in fact, there are still many people and students who congregate outside their homes and do not keep their distance for reasons of work or just to meet friends. Behaving cooperatively in the context of implementing health protocols that have been recommended by the government is very important in responding to current conditions. Trust in the government is one of the causes of the low level of cooperation in implementing health protocols during the pandemic by students. This type of research is a quantitative research using a non-experimental causal research design. The measuring instrument used in this study the institutional trust which was developed by Rosiana et al., (2018) and has been modified by the researcher by adding 1 item and cooperative behavior from BPS (2020). The research subjects were active students of the Islamic University of Bandung, amounting to 181 respondents. Data analysis using Simple Linear Regression test. The results of the study show that there is an influence of 47.9% between institutional trust on cooperative behavior in the context of implementing health protocols. Abstrak. Covid-19 merupakan penyakit menular yang disebabkan oleh coronavirus. Menyikapi pandemi covid-19, pemerintah berupaya keras menerapkan aturan 3M yaitu memakai masker, mencuci tangan dan menjaga jarak. Namun nyatanya, masih banyak masyarakat dan mahasiswa yang berkerumun di luar rumah dan tidak menjaga jarak dengan alasan bekerja ataupun hanya sekedar untuk bertemu dengan teman. Berperilaku kooperatif dalam konteks penerapan protokol kesehatan yang telah dihimbau oleh pemerintah sangat penting dalam menyikapi kondisi seperti saat ini. Kepercayaan pada pemerintah menjadi salah satu penyebab rendahnya tingkat kerjasama dalam menerapkan protokol kesehatan di masa pandemi oleh mahasiswa. Jenis dari penelitian ini merupakan penelitian kuantitatif dengan menggunakan desain penelitian kausal non eksperimental. Alat ukur yang digunakan pada penelitian ini yaitu institutional trust yang di kembangkan oleh Rosiana et al., (2018) dan telah di modifikasi oleh peneliti dengan menambahkan 1 item dan perilaku kooperatif dari BPS (2020). Subjek penelitian adalah mahasiswa aktif Universitas Islam Bandung yang berjumlah 181 responden. Analisis data dengan menggunakan uji Regresi Linier Sederhana. Hasil dari penelitian menunjukan terdapat pengaruh sebesar 47,9% antara institutional trust terhadap perilaku kooperatif dalam konteks penerapan protokol kesehatan.